1978
DOI: 10.2337/diab.27.9.959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pancreatic Islet Transplantation on the Increased Urinary Albumin Excretion Rates in Intact and Uninephrectomized Rats with Diabetes Mellitus

Abstract: The effects of reduced renal mass and of islet transplantation on urinary albumin excretion (UAE) rates in diabetic rats were examined. Increased UAE rates were noted two months after the induction of streptozotocin diabetes in 100-gm. inbred Lewis rats. Over the subsequent seven months, UAE rates remained constant in controls but were increasing in diabetic rats at the end of this time. Uninephrectomized nondiabetic rats had increasing UAE with time as compared with intact controls. Uninephrectomized diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 8 publications
6
23
1
Order By: Relevance
“…These include increased glomerular filtration rate (GFR) [1-13], increased urinary albumin excretion (UAE) [13][14][15][16][17], increased production of vasoactive prostaglandins (PGs) by renal glomeruli [10,[18][19][20], and increased glomerular sorbitol accumulation [21]. Although there are several plausible ways in which these changes could be related, the data linking these phenomena have been conflicting and confusing.…”
mentioning
confidence: 99%
“…These include increased glomerular filtration rate (GFR) [1-13], increased urinary albumin excretion (UAE) [13][14][15][16][17], increased production of vasoactive prostaglandins (PGs) by renal glomeruli [10,[18][19][20], and increased glomerular sorbitol accumulation [21]. Although there are several plausible ways in which these changes could be related, the data linking these phenomena have been conflicting and confusing.…”
mentioning
confidence: 99%
“…The influence of islet transplantation on established renal glomerular lesions has been shown in a series of experiments in diabetic rats by Mauer et al [167,281,289] and Steffes et at. [282,290].…”
Section: Effect Of Pancreas and Islet Transplantation On Long Termentioning
confidence: 99%
“…The latent period between transplantation and reversal of diabetes also depends upon the quantity of tissue transplanted, the site of transplantation, and the severity of diabetes [113,123,166]. The period can range from a few days to weeks, but if a sufficient quantity of dispersed neonatal pancreas is transplanted, permanent normoglycaemia occurs [110-117, 142, 166-168], glycosuria is abolished [110,116,123,168], weight gain is restored [110,113,116,166], and other metabolic abnormalities disappear [142,167,168].…”
Section: Dispersed Adult Pancreas Without Islet Purificationmentioning
confidence: 99%
“…During the period of study for 5 weeks normal animals showed a rise in Urinary albumin levels. This indicates progressive nephropathy 18,19 . The treatment with MESA has shown the protective effect on the elevated Urinary albumin level.…”
Section: Fig A-e: Histopathology Of Kidneymentioning
confidence: 99%